2021
DOI: 10.3390/plants10081494
|View full text |Cite
|
Sign up to set email alerts
|

Mercury-Induced Phytotoxicity and Responses in Upland Cotton (Gossypium hirsutum L.) Seedlings

Abstract: Cotton is a potential and excellent candidate to balance both agricultural production and remediation of mercury-contained soil, as its main production fiber hardly involves into food chains. However, in cotton, there is known rarely about the tolerance and response to mercury (Hg) environments. In this study, the biochemical and physiological damages, in response to Hg concentrations (0, 1, 10, 50 and 100 µM), were investigated in upland cotton seedlings. The results on germination of cottonseeds indicated th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Treatment with Hg alone slightly inhibited root growth ( Figure 1 A). This confirms the phytotoxic effect of Hg even at low levels [ 19 ]. Se induces phytotoxicity only at high concentrations [ 20 ].…”
Section: Resultssupporting
confidence: 81%
“…Treatment with Hg alone slightly inhibited root growth ( Figure 1 A). This confirms the phytotoxic effect of Hg even at low levels [ 19 ]. Se induces phytotoxicity only at high concentrations [ 20 ].…”
Section: Resultssupporting
confidence: 81%
“…H. americanus did not show germination inhibition in the 4.0 mg/L Hg treatment, indicating a higher tolerance. Other tree and shrub species such as Gossypium hirsutum (cotton) were able to maintain 80% germination at 200 mg/kg Hg [ 43 ], and Quercus ilex did not have decreased germination at 10 mg/kg Hg, but its root length was reduced at 1.0 mg/kg Hg [ 44 ]. On the other hand, the neotropical tree Plathymenia reticulate (Fabaceae), from the Brazilian Cerrado reduced its germination by 80% when exposed to 10 −3 M HgCl 2 for 72 h [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sergio et al reported that trace metal elements cause the plasmolysis and an obvious thickening of cell wall due to the harmful influences on the intracellular structure of bryophytes 40 . Vecchia et al found that most of the damage caused by trace metal elements was related to biological membrane, resulting in that the organelles with abundance in membrane structure are more vulnerable to serious damage than other structures 25 . Among many membrane-abundance organelles, chloroplasts and mitochondria may be the most severely damaged organelles by trace metal elements, because the latter hindered the division and expansion of these two organelles, as well as affected their shape and arrangement of the cystoid system 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of Hg used in previous studies related to negative effects on plants ranged up to 100 µM 25 27 . Therefore, we conducted a pre-experiment with Hg concentration gradients (0, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80 µM, the Hg treatment, obtained using HgCl 2 (Analytical Reagent) water (DI) solution).…”
Section: Methodsmentioning
confidence: 99%